The evaluation of a Taiwanese training program in smoking cessation and the trainees' adherence to a practice guideline - Leung Kai-Kuen; Chang Chih-Jen; Hung Ling-Yu; Guo Fei-Ran; Chen Ching-Yu (BMC, 2010)
Abstract Background The Taiwanese government began reimbursement for smoking cessation in 2002. Certification from a training program was required for physicians who wanted reimbursement. The program certified 6,009 physicians till 2007. The objective of this study is to evaluate the short- and long term efficacy of the training program. Methods For short term evaluation, all trainees in 2007 were recruited. For long term evaluation, computer randomly selected 2,000 trainees who received training from 2002 to 2006 were recruited. Course satisfaction, knowledge, confidence in providing smoking cessation services and the adherence to a practice guideline were evaluated by questionnaires. Results Trainees reported high satisfaction with the training program. There was significant difference between pre- and post-test scores in knowledge. Confidence in providing services was lower in the long term evaluation compared to short term evaluation. For adherence to a practice guideline, 86% asked the status of smoking, 88% advised the smokers to quit, 76% assessed the smoker's willingness to quit, 59% assisted the smokers to quit, and 60% arranged follow-up visits for smokers. The incentive of reimbursement was the most significant factor affecting confidence and adherence. Conclusions The training program was satisfactory and effective. Adherence to a practice guideline in our study was better than studies without physician training in other countries.